Destabilizing impacts of herding behaviour in Portuguese capital market - Gabriela Marques Leite; Carlos Machado-Santos; Amélia Ferreira da Silva (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
The present work seeks to analyze the herding behavior phenomenon as a destabilizing factor of the capital market, while studying the relation between the herding behavior phenomenon and market profitability and volatility. The results allow us to verify the existence of a significant intensity of herding, especially when price variation occurs. Conversely, asymmetrical and elevated volatility levels ensue, with a higher probability of profit than losses of the same magnitude. However, results are less visible when one looks at the causality relation between herding and market volatility. This paper contributes to a deeper understanding of herding behavior and its relation with market efficiency.
Keywords: G50; 330; herding behavior; behavioral finances; volatility; capital markets; investors rationality